1996
DOI: 10.1007/bf01718637
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus G and P types circulating in Brazil: characterization by RT-PCR, probe hybridization, and sequence analysis

Abstract: We used reverse transcription-polymerase chain reaction (RT-PCR) to determine the P and G genotypes of 130 culture-adapted rotavirus strains isolated from 181 fecal specimens of children under 5 years of age from 9 states and the Federal District of Brazil. The 4 genotypes found most commonly worldwide were also common in Brazil and P[8]G1 was the most prevalent (43%), followed by P[4]G2 (12%), P[8]G3 (6%), and P[8]G4 (6%). However, unusual types P[8]G5, P[6]G2, P[9]G1, P[9]G3, and mixed infections were respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
180
4
9

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(204 citation statements)
references
References 41 publications
11
180
4
9
Order By: Relevance
“…RVA screening was performed using the EIA IDEA Rotavirus (Oxoid Ltd, England) and/or RIDASCREEN Rotavirus (R Biopharm Group, Germany) kits and PAGE. The semi-nested PCR for the RVA G and P genotyping were performed as previously described (Gentsch et al 1992, Das et al 1994, Leite et al 1996. NoV PCR was used to screen for NoV and was based on the degenerate primers Mon 431-434, which are specific to region B and are located within the 3'-end of open reading frame (ORF)1 (RNA polymerase) (Beuret et al 2002).…”
mentioning
confidence: 99%
“…RVA screening was performed using the EIA IDEA Rotavirus (Oxoid Ltd, England) and/or RIDASCREEN Rotavirus (R Biopharm Group, Germany) kits and PAGE. The semi-nested PCR for the RVA G and P genotyping were performed as previously described (Gentsch et al 1992, Das et al 1994, Leite et al 1996. NoV PCR was used to screen for NoV and was based on the degenerate primers Mon 431-434, which are specific to region B and are located within the 3'-end of open reading frame (ORF)1 (RNA polymerase) (Beuret et al 2002).…”
mentioning
confidence: 99%
“…The first period included 653 RV-A-positive samples that were collected from 1982-1995; these cases were reported in 15 papers in our literature review (Linhares et al 1988, Stewien et al 1994, Gusmão et al 1995, Leite et al 1996, Mascarenhas et al 1998, Cardoso et al 2000, 2001, Carmona et al 2004. The second period included 1,839 RV-A-positive samples that were collected from 1996-2005; these cases were reported in 19 articles in our literature review (Santos et al 1998, 2005b, Araújo et al 2002, Rosa-e-Silva et al 2002, Souza et al 2003, Luz et al 2005, Carmona et al 2006, Carvalho-Costa et al 2006, 2009, Pietruchinski et al 2006, Andreasi et al 2007, Gouvea et al 2007, Montenegro et al 2007, Martini et al 2008, Domingues et al 2008, Ribeiro et al 2008.…”
mentioning
confidence: 99%
“…Uncommon or emergent RV-A genoytpes, which are found mainly in developing countries, trigger discussions about the potential efficacy, in some regions, of the vaccines that were undergoing clinical trials during the early 1990s (Leite et al 1996, Gouvea & Santos 1999. The rationale for the development of the rhesus-human tetravalent reassortant vaccine (RRV-A-TV, Rotashield™), for instance, was that its multivalent composition would target the classical genotypes G1-4.…”
mentioning
confidence: 99%
“…Mascarenhas et al 26 , studying samples from Belém, in the state of Pará, found that 41% of the P genotypes were mixtures. In a study by Leite et al 23 , samples from nine states in southern, southeastern, northeastern and central Brazil were genotyped, and 21% of the genotypes were found to be mixtures.…”
Section: Discussionmentioning
confidence: 99%